PERAN AKUNTAN FORENSIK, AUDIT INVESTIGATIF DAN SKEPTISISME PROFESIONAL TERHADAP PENDETEKSIAN FRAUD DI INDONESIA - Wiwit Lestari; Estralita Trisnawati (Fakultas Ekonomi Universitas Tarumanagara, 2024)
This study aims to determine whether the role of forensic accountants, investigative audit and professionalskepticism has a positive effect on fraud detection in Indonesia. This study used a purposive sampling technique indetermining a sample of 110 respondents. This study used a quantitative approach and a questionnaire as aresearch instrument with research objects on the perceptions of practitioners from the Indonesian Association ofCertified Fraud Examiners (ACFE) and auditors in Indonesia. Hypothesis testing was carried out using multiplelinear regression tests using IBM SPSS 26. The results of this study indicate that the role of forensic accountantshas no significant effect, while investigative auditing and professional skepticism have a significant effect on frauddetection in Indonesia. This study suggests to future researchers to add the variables of gender, age, educationalbackground, and years of service as evidenced by this research that these criteria have a significant effect and canexplain the dependent variable. For further research, you can refer to this research as a source of literatureregarding references, knowledge and information about the importance of implementing the role of forensicaccountants, investigative audits and professional skepticism in fraud detection in Indonesia.